2017
DOI: 10.3892/etm.2017.4304
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MALAT1 is upregulated and involved in cell proliferation, migration and apoptosis in ovarian cancer

Abstract: Abstract. Ovarian cancer (OC) is the leading cause of mortality among gynecological malignancies. Although microRNAs are known to have a key regulatory role in OC, the involvement of long non-coding RNAs in the disease is less established. Previous studies have demonstrated that metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a tumor oncogene in many cancers, though its role in OC remains unclear. The present study reported that MALAT1 expression was markedly upregulated in OC, by knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…As above reported, MALAT1, a lncRNA, previously related to ovarian cancer [ 22 , 23 , 24 , 25 , 26 , 27 ], and to epithelial to mesenchymal transition (EMT) [ 28 ], was detected in our results of EOC-HMGB1-interactome ( Table 1 ). We verified by sequencing that the micropeptide derived from MALAT1 lncRNA, MTEVEMKLLHGVKNVFKRKLRERTTEPRINTNRRAMLLD, is in frame and fused to GAL4 in the recovered Y2H clone.…”
Section: Resultssupporting
confidence: 78%
“…As above reported, MALAT1, a lncRNA, previously related to ovarian cancer [ 22 , 23 , 24 , 25 , 26 , 27 ], and to epithelial to mesenchymal transition (EMT) [ 28 ], was detected in our results of EOC-HMGB1-interactome ( Table 1 ). We verified by sequencing that the micropeptide derived from MALAT1 lncRNA, MTEVEMKLLHGVKNVFKRKLRERTTEPRINTNRRAMLLD, is in frame and fused to GAL4 in the recovered Y2H clone.…”
Section: Resultssupporting
confidence: 78%
“…MALAT1 expression levels are dysregulated in a variety of cancers, including HCC, 31 , 32 renal cell carcinoma, 33 cholangiocarcinoma, 34 pancreatic cancer, 35 , 36 lung cancer, 37 , 38 gastric cancer, 39 , 40 oral squamous cell carcinoma 41 and ovarian cancer. 42 – 44 In our previous study, we found that MALAT1 was upregulated in breast cancer tissues and cancer cell lines, 45 but MALAT1 interaction with other tumor cells in the tumor microenvironment still needs further study. In the present study, we revealed tumor cells secreted MALAT1 to recipient cells to regulate receptor cell proliferation in tumor microenvironment.…”
Section: Discussionmentioning
confidence: 97%
“…Jin et al (34) have reported that MALAT1 promotes epithelial OC cell proliferation and metastasis via modulation of the PI3K-AKT pathway. Wu et al (35) have also shown that MALAT1 is elevated in OC and is involved in cell proliferation, apoptosis, and migration. However, the molecular mechanisms underlying MALAT1 in OC progression, especially the interaction between MALAT1 and miRNA, are not fully understood.…”
mentioning
confidence: 95%